Fetal alcohol spectrum disorders and access to regional center services in San Diego County. (14th September 2022) - Montag, Annika C.; Jones, Kenneth Lyons; del Campo, Miguel; Akshoomoff, Natacha; Coles, Claire D.; Kable, Julie A.; Hernandez, John‐Gregorey; Chambers, Christina D.
Abstract: Background: Fetal alcohol spectrum disorders (FASD) are developmental disabilities that are estimated to occur in 2–5% of elementary school children and that negatively impact a child's ability to function without support. Timely diagnosis‐informed interventions are crucial to optimizing the developmental trajectory of children with FASD. The true prevalence of FASD among children receiving services for developmental disabilities is unknown. Methods: An FASD prevalence study was carried out between 2011 and 2014 among a sample of 5‐ to 7‐year‐old children who were receiving services provided by the California State Regional Center for Developmental Disabilities in San Diego County. Children whose parent or caregiver consented were evaluated using the Collaboration on Fetal Alcohol Spectrum Disorders Prevalence study assessment protocol and classification criteria. Results: Among 216 eligible caregiver‐child dyads, 44 completed assessments that were sufficient to obtain a classification for FASD, including fetal alcohol syndrome (FAS), partial FAS, alcohol‐related neurodevelopmental disorder, or no fetal alcohol spectrum disorder. Fifteen children were classified as meeting the criteria for an FASD. A minimum FASD prevalence rate of 69.4 per 1000 (6.9%) among all eligible children was estimated. None of the children classified as FASD were receiving services because of an FASD diagnosis, and none had previously been diagnosed with FASD. Autism was the most common qualifying diagnosis for which children classified as FASD were receiving services. Conclusions: The 6.9% prevalence estimate among Regional Center clients was higher than the prevalence estimate of 2.3% in the same community among 5‐ to 7‐year‐old children in the general population, though the estimate was based on only 20% of eligible dyads. All children in the sample were receiving Regional Center services for another diagnosis. Barriers to eligibility for services for children with FASD may lead to less than optimum care for these children. Study findings support the facilitation of access to developmental services for children with FASD. Abstract : An FASD prevalence study was carried out among a sample of 5‐7‐year old children receiving services provided by the California State Regional Center for Developmental Disabilities in San Diego County. Among 216 eligible children, 44 completed assessments, and fifteen met criteria for an FASD. A minimum FASD prevalence rate of 69.4 per 1, 000 (6.9%) was estimated. None of the children identified had previously been diagnosed with FASD. Study findings support facilitation of access to developmental services for children with FASD.